2023
DOI: 10.1038/s41467-023-37911-0
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus mRNAs encode determinants for nuclear export via the cellular TREX-2 complex

Abstract: Nuclear export of influenza A virus (IAV) mRNAs occurs through the nuclear pore complex (NPC). Using the Auxin-Induced Degron (AID) system to rapidly degrade proteins, we show that among the nucleoporins localized at the nucleoplasmic side of the NPC, TPR is the key nucleoporin required for nuclear export of influenza virus mRNAs. TPR recruits the TRanscription and EXport complex (TREX)−2 to the NPC for exporting a subset of cellular mRNAs. By degrading components of the TREX-2 complex (GANP, Germinal-center A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…IAV mRNA synthesis is further complicated by the fact that, minimally, 8 out of the 10 predominant IAV mRNAs are not spliced. 20 Splicing in eukaryotic cells generally leads to the direct recruitment of nuclear export factors such as NXF1 followed by the rapid trafficking of spliced mRNA to the cytoplasm. 21 However, this is not the case for the majority of IAV transcripts, and successful replication necessitates other means to effectively export IAV mRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IAV mRNA synthesis is further complicated by the fact that, minimally, 8 out of the 10 predominant IAV mRNAs are not spliced. 20 Splicing in eukaryotic cells generally leads to the direct recruitment of nuclear export factors such as NXF1 followed by the rapid trafficking of spliced mRNA to the cytoplasm. 21 However, this is not the case for the majority of IAV transcripts, and successful replication necessitates other means to effectively export IAV mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study has implicated a role for the TREX-2 complex in the nuclear-cytoplasmic trafficking of IAV mRNAs. 20 The authors found that the nucleoporin, TPR, is important for this process via its recruitment of TREX-2 to the nuclear pore complex (NPC). For a subset of cellular mRNAs, and it seems IAV mRNAs, that are exported via this process, NXF1 is recruited by GANP, a component of TREX-2, which then leads to mRNA trafficking through the NPC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-termini of these proteins are anchored to the nuclear pore, and their C-termini extend roughly 300 nm into the nuclear interior (Bangs et al, 1998; Kim et al, 2018). In addition to the purported roles in retaining immature RNAs in the nucleus, Mlp1p and TPR have been implicated in mRNA export in S. pombe , Arabidopsis , and mammalian cells as perturbations of these proteins result in the accumulation of poly(A)+ RNA in the nucleus and/or defects in export of specific mRNAs to the cytoplasm (Aksenova et al, 2020; Bae et al, 2009; Bhat et al, 2023; Lee et al, 2020; Li et al, 2021; Shibata et al, 2002; Umlauf et al, 2013; Xu et al, 2007; Zuckerman et al, 2020). Indeed, rapid depletion of TPR and NXF1 results in similar mRNA export defects (Aksenova et al, 2020; Zuckerman et al, 2020), supporting an mRNA export role for TPR, which microscopy implies functions in mRNA docking to the NPC (Aksenova et al, 2020; Lee et al, 2020; Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%